Rare earth doping of topological insulators: A brief review of thin film and heterostructure systems - Hesjedal, T (Wiley, 2019)
Magnetic topological insulators (MTIs) are a novel materials class in which a topologically nontrivial electronic band structure coexists with long‐range ferromagnetic order. The ferromagnetic ground state can break time‐reversal symmetry, opening a gap in the topological surface states whose size is dependent on the magnitude of the magnetic moment. Doping with rare earth ions is one way to introduce higher magnetic moments into a material, however, in Bi2Te3 bulk crystals, the solubility limit is only a few percent. Using molecular beam epitaxy for the growth of doped (Sb,Bi)2(Se,Te)3 TI thin films, high doping concentrations can be achieved while preserving their high crystalline quality. The growth, structural, electronic, and magnetic properties of Dy, Ho, and Gd doped TI thin films will be reviewed. Indeed, high magnetic moments can be introduced into the TIs, which are, however, not ferromagnetically ordered. By making use of interfacial effects, magnetic long‐range order in Dy doped Bi2Te3, proximity‐coupled to the MTI Cr:Sb2Te3, has been achieved. Clearly, engineered MTI heterostructures offer new possibilities that combine the advantageous properties of different layers, and thus provide an ideal materials platform enabling the observation new quantum effects at higher temperatures.